Network for integrating Virtual Mobility and European Qualification Framework in HE and CE Institutions: The VIRQUAL Project - Carme Royo (2011)
The main objectives of VIRQUAL are to help educational and training institutions to (a) achieve VirtualMobility, and (b) guarantee EQF implementation through eLearning. VIRQUAL promotes cooperationand joint work among partner organisations and links with related initiatives. Since summer 2010 theconsortium has concentrated in three tasks including the preparation of webinars that will take place induring 2011.Task 1: eLearnig and EQF: a comprehensive analysis of the EQF implementation in Europe compiling32 country reports on EQF/NQF implementation, at levels 5 to 8 has been collected. Additionally, thesituation of e-learning in what concerns legislation and practice in each of the 32 countries was alsoreported. The analysis of the information pack will allow access to updated information on EQF,recognition of competences and e-learning legislation by country as a consulting instrument.Task 2: Three webinars, each one with one expert invited speaker on the general theme of e-learningand EQF followed by an online discussion with the participants and with the participation in otherdissemination events.Task 3: How can we support teachers and curriculum developers defining, writing, or choosing highquality learning outcomes? How can we contribute to a global architecture of learningoutcomes/competences? What is a useful classification system for learning outcomes/competences?The means to answer these questions is a web-based data base, the ILO repositorywww.learning-outcomes.net. One of the fundaments of its data structure is the classification oflearning outcomes according to EQF which distinguishes knowledge, skills and competences.